The Relationship between Industry and Universities - Mondragón Liévana, Carlos (Cuadernos de Estudios Empresariales, 2012)
In this paper, the current relationship between industry and academia is presented by reviewing the historical development of research and development labs in order to classify the linkages and strengths that emerged between universities and industry.